Eloise the flame dragon - Mara, Maddy; Foresti, Sara (New York, NY : Scholastic Inc., 2025)
Eloise learns that she is the mighty Flame Dragon. She must lead Ash and Maya on an epic quest to a place in the forest called the Fire Realm, which only appears once every one thousand years. An evil queen is gaining power there. She must be stopped--and Eloise and her friends are just the dragons for the job.
The fire dragons--Cover.
School Library Journal, December 2024
3-6
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Friendship -- Juvenile fiction; Dragons -- Fiction; Magic -- Fiction; Friendship -- Fiction; Fantasy; Fantasy fiction; Forest animals -- Fiction